2021
DOI: 10.3390/metabo11090613
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Reveals Process of Allergic Rhinitis Patients with Single- and Double-Species Mite Subcutaneous Immunotherapy

Abstract: Allergen immunotherapy (AIT) is the only treatment that can change the course of allergic diseases. However, there has not been any research on metabolic reactions in relation to AIT with single or mixed allergens. In this study, patients with allergic rhinitis caused by Dermatophagoides pteronyssinus (Der p) and Dermatophagoides farinae (Der f) were treated with single-mite (Der p) and double-mite (Der p:Der f = 1:1) subcutaneous immunotherapy (SCIT), respectively. To compare the efficacy and the dynamic chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…In terms of biomarkers for AIT, Gotoh et al 87 discovered that the levels of antigen‐specific IgE and IgG4 were increased in patients with coexisting HDM and JCP AR following SLIT tablet treatment; herein, IgE, IgG4, or IgE/IgG4 ratios have been used to predict the therapeutic effect of SCIT, 76,88–90 not serum or salivary IgA 50 . In AR patients, an increase in active antigen‐specific CD38 + B cells, able to secrete IL‐6 to convert Treg cells from Th17 cells in the presence of TGF‐β, was also considered an early marker that can be used to predict the outcome of AIT 91 .…”
Section: Mechanism‐oriented Treatmentmentioning
confidence: 99%
“…In terms of biomarkers for AIT, Gotoh et al 87 discovered that the levels of antigen‐specific IgE and IgG4 were increased in patients with coexisting HDM and JCP AR following SLIT tablet treatment; herein, IgE, IgG4, or IgE/IgG4 ratios have been used to predict the therapeutic effect of SCIT, 76,88–90 not serum or salivary IgA 50 . In AR patients, an increase in active antigen‐specific CD38 + B cells, able to secrete IL‐6 to convert Treg cells from Th17 cells in the presence of TGF‐β, was also considered an early marker that can be used to predict the outcome of AIT 91 .…”
Section: Mechanism‐oriented Treatmentmentioning
confidence: 99%
“…The second study evaluated the outcome, in AR patients with dual sensitivity, to Dermatophagoides pteronyssinus and Dermatophagoides farinae treated with SCIT, adding a metabolomics assessment to standard clinical parameters. Both treatments had therapeutic effects with no significant differences in efficacy, while a reduction in inflammation-related metabolites was constantly observed in patients undergoing SCIT treatment, highlighting arachidonic acid and its metabolites as potential biomarkers [ 26 ]. In the latter study, 68 patients completing the SLIT course were categorized into effective and ineffective groups.…”
Section: Omicsmentioning
confidence: 99%
“… Zheng et al (2021) focused on the drug treatment of 73 AR patients who were simultaneously sensitized by Der p and Der f with single-mite subcutaneous immunotherapy (SM-SCIT) or double-mite subcutaneous immunotherapy (DM-SCIT). Both treatments with SM-SCIT (35 patients) and DM-SCIT (38 patients) consisted of three administrations, leading to 219 serum samples.…”
Section: Application Of Metabolomics In Ear Nose and Throatmentioning
confidence: 99%
“…Concerning allergic rhinitis, in different studies ( Zheng et al, 2021 ; Yuan et al, 2022 ), the authors using the same approach (UPLC-QTOF-MS), found different metabolites, mostly belonging to the same pathway. However, most metabolites were related to the arachidonic acid metabolism which is considered helpful at mirroring a reduction of inflammation after therapy.…”
Section: Comments and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation